The Development of Bus Routing Recommendation Using Dynamic A* Algorithm - พงษ์ศิลป์, กมลวรรณ (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2018)
This research is experimental research. The purpose of this study was to investigate the problems and ways to develop a bus route selection mechanism. The researcher has adopted the concept of route selection with dynamic algorithms. Aster Star is used to find and select the appropriate route for the user. Help to calculate time and plan to travel efficiently. The research tool was a traffic information model developed by Swift, based on the A starts dynamic algorithm. The samples were bus traffic data, mass transit ( Routes 207, 51ร, 522 consist of: (1) Route risk; (2) Approach to take-off bus; and (3) Significance of route. Routes The results showed that the results from the expert evaluation were good ( = 4.30, S.D. = 0.27). This research can be applied to the selection of other bus routes as well as this knowledge can be extended to further academic results in the future.